Le traducteur indépendant au Japon - Kanamori, Osamu (Meta, 1988)
SummaryIn spite of large-scale and ever-increasing translation activities in Japan, professional translation is an uncertain, non-lucrative, socially not highly regarded occupation. Most free-lance translators do translation as a secondary activity. The situation may be changing with the growing number of translation schools that have opened in recent years, which may increase the number of professional translators.Most of the free-lance translation work is done through translation agencies in the technical and industrial fields, though young translators aspire to do literary translation. Other translators work for publishers who provide a significant amount of work, since foreign novels and other books are translated in very large numbers. Harlequin and Harlequin-like series also provide translation opportunities through publishers, though their quality is not up to literary standards. A significant part of translation work for publishers is actually done by "shitayaku", "sub-contractors" of the translators, whose names generally do not even appear on the book covers. These shitayaku eventually become full-fledged translators themselves.Japanese translators work mostly in isolation, though some translation school students'groups survive graduation and continue working collectively for a time. Atany rate, the image of the independent translator working little, earning much and enjoying a leisurely life is not quite true.In spite of the difficulties that young translators have to surmount and their rather uncertain professional and financial prospects, translation has a significant cultural role to play in Japanese society.